The ATP-mediated cytokine release by macrophages is down-modulated by unconventional α9* nicotinic acetylcholine receptors - Wolf, Philipp M. K.; Hanke, Dominik; Singh, Vijay K.; Keller, Hanno L.; Ettischer, Luca J.; Teppe, Laura; Amati, Anca-Laura; Hecker, Andreas; Husain-Syed, Faeq; Rohde, Marius; Nuber, Ulrike A.; Büttner, Kathrin; et al. (Frontiers in Immunology, 2025)
ObjectiveThe clinical interest in mechanisms controlling the biosynthesis and release of the pro-inflammatory cytokine interleukin (IL)-1β is outstanding, as IL-1β is associated with life-threatening inflammatory diseases including hyperinflammation caused by extracellular ATP originating from damaged cells. Previously, we identified a cholinergic mechanism controlling ATP-dependent IL-1β release via metabotropic signaling of unconventional nicotinic acetylcholine receptors (nAChRs) containing subunits α7 and α9* (denoting homomeric or heteromeric α9) in monocytes. This study examines whether this mechanism is active in human macrophages (THP-1 cell-derived, peripheral blood mononuclear cell-derived, and peritoneal macrophages).MethodsExpression of nAChR subtypes (CHRNA7, CHRFAM7A, CHRNA9, CHRNA10) was analyzed using real-time RT-PCR. The efficiency of the differentiation protocols used was assessed by surface markers and metabolic conversion rate analysis. Cholinergic control of ATP-induced IL-1β, IL-18, and IL-1α release was tested using nAChR agonists and conopeptides antagonizing α7 and α9* nAChRs.ResultsAll nAChR subunits were expressed by all cells analyzed. Activation of nAChRs efficiently inhibited the ATP-mediated IL-1β release by macrophages, while ATP-independent release remained unaffected. Moreover, the nAChR agonists inhibited the release of IL-18 and IL-1α. The inhibitory effect was reversed by subunit-specific conopeptides, indicating the involvement of unconventional nAChRs containing subunits α7 and α9*.ConclusionWe conclude that the cholinergic control of ATP-mediated IL-1β release is active in human monocytes and in macrophages and that nAChR agonists can also regulate the release of IL-18 and IL-1α. This mechanism specifically regulates the ATP-induced cytokine release, without suppressing ATP-independent cytokine release. Thus, unconventional α9* nAChRs are promising therapeutic targets for ATP-induced inflammatory diseases, including sterile hyperinflammation.